Dead cell counts during serum cultivation are underestimated by the fluorescent live/dead assay. - Zhou, S; Cui, Z; Urban, J (2011)
The live/dead fluorescent assay provides a quick method for assessing the proportion of live and dead cells in cell culture systems or tissues and is widely used. Dead cells are detected by the fluorescence produced when propidium iodide (PI) binds to DNA; PI and similar molecules are excluded from live cells but can penetrate dead cells because of their loss of membrane integrity. Here we investigated the effect of serum in the culture medium on the reliability of the method. We assessed viability of chondrocytes with/without serum using both a live/dead assay kit and also trypan blue staining. We found that after 2 days of culture, the DNA-binding dye PI could no longer detect dead cells if serum was present but they were readily detected in serum-free medium or if an inhibitor to DNase I was added to the serum-containing medium. Dead cells could be detected by trypan blue staining in all cultures. Hence dead cells are no longer detected as the DNase I present in serum degrades their DNA. DNA-binding dyes may thus not give a reliable estimate of the number of dead cells in systems that have been cultured in the presence of serum for several days.